HOW THE ENDOCRINE SYSTEM AND MICROBIOTA EXPLAIN THE EMOTIONS BIOCHEMISTRY AND THEIR IMPACT IN HEALTH - Linhares, Guilherme T.; Lima, Elsa S.; Perico, Camila P.; Filho, Antonio C. Da Silva; De Pierri, Camilla R.; Raittz, Roberto T.; Guizelini, Dieval; Marchaukoski, Jeroniza N. (ARACÊ, 2024)
Emotional reactions stimulate neural circuits and biological pathways that produce neurotransmitters, affecting homeostasis and promoting disease. Health and emotions communicate, establishing a bidirectional cause-and-effect pathway. The composition of the microbiota also affects health and emotions, interacting through metabolites, such as short-chain fatty acids (SCFA), with the host's biochemistry. Certain genera of bacteria act in different ways on the host's homeostasis, keeping the immune system constantly vigilant and acting on the synthesis of neurotransmitters, such as serotonin and dopamine, which are responsible for well-being. When the host is in homeostasis, the synthesis of neurotransmitters is normal, which keeps the intestinal microbiota in balance. However, when the organism is out of balance, this synthesis is impaired; decreasing the concentration of the initial compounds for the production of neurotransmitters, which leads to a reduction in the concentration of neurotransmitters and exaggerated activation of the HPA axis, inducing an imbalance in the intestinal microbiota, generating dysbiosis. Due to dysbiosis, the synthesis of neurotransmitters is impaired, leading the host to develop mental disorders such as depression, anxiety and chronic stress; which contributes to the state of imbalance of the organism, harming mental and physical health. By adequately restoring the intestinal microbiota, the hyperactivation of the HPA axis decreases, returning the body to homeostasis, resulting in the improvement of symptoms of depression, anxiety and chronic stress; leaving the organism healthy, both mentally and physically. Therefore, in this study we contextualize emotional research from a historical and descriptive perspective and present the main models of emotional identification. Focusing on basic emotions, we research the relationship of emotional states with the HPA axis and the microbiota, as well as how the bacteria present in the intestine affect the well-being of the host. Finally, we discuss our analysis presenting the bidirectional relationship between the endocrine system, microbiota and emotions.